Tecnologias de redes municipais sem fio - Mazur, Gilmar (2012)
This research presents a study of wireless network technologies, applied to municipal networks. The willingness of governments of deploying these networks, has demonstrated their importance in serving citizens, enterprises and public institutions but also to solve the problem of digital exclusion. Shown are two wireless technologies for long distance (WiMAX and WiMesh), which can meet the needs of municipal networks.